Design of Remote Open Control Scheme for Fully Automatic Unmanned Subway - Yuhang JING; Jianhui HUANG; Shangzhuo SI; Li ZHOU (机车电传动)
In order to solve the problem that the air circuit breaker cannot be manually reset in fully automatic unmanned subway vehicles, in view of the characteristics of the fully automatic unmanned system, the air circuit breaker matrix monitoring solution and the air circuit breaker remote reset solution were proposed in this paper. The program has been practically applicated to unmanned subway vehicles on Shanghai line 18 and achieved good results.